Replication Requires Psychological Rather than Statistical Hypotheses: The Case of Eye Movements Enhancing Word Recollection - Phaf, R. Hans (Frontiers in Psychology, 2016)
Can an experiment be replicated in a mechanical fashion without considering the processes underlying the initial results? Here I will consider a nonreplication of Saccade Induced Retrieval Enhancement (SIRE) and argue that it results from focusing on statistical instead of on substantive process hypotheses. Particularly the theoretical integration of SIRE with Eye-Movement Desensitization and Reprocessing therapy (EMDR), provides clues about when the memory enhancement should occur. A relatively large memory enhancement effect in participants with a consistent (i.e., extreme right or left) handedness should be observed, a) when explicitly instructed to retrieve and imagine the memories during the eye manipulation, and b) for emotionally negative material. A finer theoretical analysis may thus well explain the contrast between the original SIRE studies and the nonreplication. Also the findings from preregistered confirmatory research (i.e., focusing solely on statistical hypotheses) should be considered preliminary, representing shifts on a gradual scale of evidence, and awaiting interpretation in terms of theoretical hypotheses. Stronger, but still not definitive, conclusions can better be postponed until after multi-study meta-analyses with theoretically motivated moderator variables have been performed.